Who makes a good leader? Cooperativeness, optimism and leading-by-example - Simon Gächter; Daniele Nosenzo; Elke Renner; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2009)
We examine the characteristics of effective leaders in a simple leader-follower voluntary contributions game. We focus on two factors: the individual's cooperativeness and the individual's beliefs about the cooperativeness of others. We find that groups perform best when led by those who are cooperatively inclined. Partly this reflects a false consensus effect: cooperative leaders are more optimistic than non-cooperators about the cooperativeness of followers. However, cooperative leaders contribute more than non-cooperative leaders even after controlling for optimism. We conclude that differing leader contributions by differing types of leader in large part reflects social motivations
Keywords: A13; C92; D03; 330; Führungspersönlichkeit; Kooperation; Vertrauen; Spieltheorie